Oropharyngeal Branchial Cyst in a Young Child - ÇALIM, ÖMER FARUK; SOYLU, Erkan; ORHAN, Israfil; YILMAZ, Fahrettin; CAKIR, Asli; Calim, Omer Faruk (My University, 2014)
Second branchial cleft cysts are almost always located in the neck. Their presence in the oropharynx is extremely rare. An oropharyngeal branchial cyst in a 4-year-old child diagnosed by magnetic resonance and histopathology was presented. Anatomic location and pathological findings indicated the second branchial pouch origin. The cyst was excised transorally. Six months- follow-up of the child was uneventful and there was no recurrence.